The role of dopamine release and D2 dopamine receptor in GHRH and somatostatin cells in controlling growth hormone secretion - de Souza, Gabriel O.; Gusmao, Daniela O.; de Sousa, Maria E.; Martins, Marina G.; Basso, Alexandre S.; Donato, Jose (Frontiers in Endocrinology, 2026)
IntroductionPituitary growth hormone (GH) secretion is primarily controlled by GH-releasing hormone (GHRH) and somatostatin (SST), peptides produced by hypothalamic neurons. Evidence indicates that dopamine also modulates GH secretion, potentially via D2 dopamine receptor (D2R). Additionally, a subset of GHRH neurons in the arcuate nucleus of the hypothalamus expresses tyrosine hydroxylase (TH), the rate-limiting enzyme of dopamine biosynthesis. However, the role of dopamine release from GHRH neurons and the neuronal population that expresses D2R to regulate GH secretion remain currently unknown.MethodsMice lacking TH specifically in GHRH cells were generated.ResultsGHRHΔTH mice display relatively normal body growth and pulsatile GH secretion compared to control animals. Next, the effects of D2R deletion in GHRH or SST neurons were examined. GHRHΔDrd2 male mice tended to have reduced lean mass and increased adiposity compared to controls, along with decreased basal GH secretion. SSTΔDrd2 male mice also exhibited reduced body weight and lean mass. Total and pulsatile GH secretion, as well as serum insulin-like growth factor 1 (IGF-1) levels, were not different between groups. No significant differences in body growth, GH secretion pattern, and serum IGF-1 concentration were observed among control, GHRHΔDrd2, and SSTΔDrd2 females.DiscussionDopamine production in GHRH neurons is not necessary for regulating body growth or GH secretion. D2R ablation in GHRH or SST neurons has a small impact on lean mass and GH secretion, indicating that these neurons mediate only a minor part of the effects induced by complete D2R absence in male mice.